2017
DOI: 10.5614/j.math.fund.sci.2017.49.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Indigofera tinctoria L. in Java and Madura Islands as Natural Batik Dye based on Inter-simple Sequence Repeat Markers

Abstract: Abstract. Indigo leaves (Indigofera tinctoria L.) are utilized as a source of batik dye in Java and Madura islands, Indonesia. Batik makers from the islands collect indigo leaves from wild plants. Continuous collection of wild plants from their natural habitat may decrease their diversity. The present research was conducted to analyze the genetic diversity and population structure of I. tinctoria L. from Java and Madura. 55 indigo accessions were collected from 10 locations in Java and Madura. The indigo DNA w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 9 publications
0
8
0
4
Order By: Relevance
“…Hal ini berarti susunan basa dengan pola (AC) 8 TG memiliki sekuens komplemen lebih sedikit dibandingkan dengan susunan basa yang berpola (AC) 8 T pada genom sayuran polong. Primer PKBT 3 dan PKBT 6 merupakan primer informatif karena sekuen primer memilki banyak kecocokan dengan urutan basa mikrosatelit yang terdapat pada sampel tanaman maupun genom tanaman lainnya, seperti anggrek (Romeida et al, 2012), manggis (Sulassih et al, 2013) dan tarum (Hariri et al, 2017).…”
Section: Hasil Dan Pembahasan Analisis Dan Profil Penanda Molekuler Issrunclassified
See 1 more Smart Citation
“…Hal ini berarti susunan basa dengan pola (AC) 8 TG memiliki sekuens komplemen lebih sedikit dibandingkan dengan susunan basa yang berpola (AC) 8 T pada genom sayuran polong. Primer PKBT 3 dan PKBT 6 merupakan primer informatif karena sekuen primer memilki banyak kecocokan dengan urutan basa mikrosatelit yang terdapat pada sampel tanaman maupun genom tanaman lainnya, seperti anggrek (Romeida et al, 2012), manggis (Sulassih et al, 2013) dan tarum (Hariri et al, 2017).…”
Section: Hasil Dan Pembahasan Analisis Dan Profil Penanda Molekuler Issrunclassified
“…Hasil penelitian menunjukkan persentase pita polimorfik pada populasi interspesifik memiliki persentase polimorfis lebih tinggi (Thul et al, 2012) bila dibandingkan dengan populasi intraspesifik (Rana et al, 2014). Menurut Hariri et al (2017) Hasil analisis hubungan genetik pada tingkat interspesifik lebih menunjukkan keragaman yang lebih tinggi dibandingkan pada tingkat intraspesifik. Pada tingkat kemiripan 44.40-70.00% menunjukkan bahwa antar spesies sayuran polong berada pada kelompok yang berbeda, sedangkan pada tingkat kemiripan 91.25-97.50% menunjukkan bahwa antar aksesi dalam spesies yang sama berada pada kelompok yang berbeda.…”
Section: Hasil Dan Pembahasan Analisis Dan Profil Penanda Molekuler Issrunclassified
“…DNA from dried rambutan leaves were extracted according to Cetyl Trimethyl Ammonium Bromide (CTAB) protocol (Doyle 1991) with several modifications by Hariri (2017), Souza et al (2012) and Riupassa (2016). The modification included the addition of Sorbitol buffer before CTAB buffer extraction to minimize the high mucus content of the leaves, and also the addition of repeated DNA purification process to separate polysaccharide and other secondary metabolite residues from the DNA samples.…”
Section: Dna Isolation Amplification and Visualizationmentioning
confidence: 99%
“…The modification included the addition of Sorbitol buffer before CTAB buffer extraction to minimize the high mucus content of the leaves, and also the addition of repeated DNA purification process to separate polysaccharide and other secondary metabolite residues from the DNA samples. Six out of 31 ISSR primers (Degani et al 2003, Hariri 2017, Riupassa 2016 were selected to produce the clearest and showed the highest polymorphic INTRODUCTION Rambutan (Nephelium lappaceum L.) is one of tropical fruit that has a high potential value. It belongs to Sapindaceae which originated from South East Asia primarily in Indonesia and Malaysia (Leenhouts, 1986).…”
Section: Dna Isolation Amplification and Visualizationmentioning
confidence: 99%
“…tinctoria is from the Fabaceae family, which is efficacious as a natural dye industry. The plant is used as a natural dye agent in the textile industry because it contains indigo pigments that produce indigo colors [3]. I. tinctoria natural dyes were the main product of India and West Africa before the discovery of synthetic indigo.…”
Section: Introductionmentioning
confidence: 99%